Seismic Response Analysis of Secondary Lining Polymer Grouting Debonding Repair for Tunnel Construction Based on Parameter Inversion - Fengyang Miao; Chunyu Liang; Weiguo Li; Zhengxuan Huang; Jianguo Xu; Yingchun Cai; Xiaoyu Feng; Yiming Xu (Advances in Civil Engineering)
The void phenomenon behind the tunnel lining has become the main cause of tunnel disease, easily triggering tunnel lining structure damage, shedding, water seepage, and other diseases that seriously threaten the normal operation of the tunnel. The void area behind the lining seriously reduces the seismic capacity of the tunnel. In this paper, the mechanical parameters of the surrounding rock are calculated by optimizing the inversion of the improved system identification sensitivity analysis method, and the numerical model of the tunnel’s dynamic response is optimized using the improved inversion results to study the repair effect and seismic capacity of the Longmenshan tunnel using polymer grouting to repair the void area behind the lining under the action of a seismic load. The results show that the displacement and stress at the top of the tunnel secondary lining void area are significantly reduced and close to normal after the repair of polymer grouting; however, the stress and displacement at the top of the secondary lining are significantly different under the action of seismic waves at the same peak at different site conditions, which indicates that the dynamic response of this tunnel model has obvious sensitivity to the seismic wave spectrum.